Etiology, Epidemiology and Management of Diseases: Warfare Between the Pathogen and the Pathologist - Larbi-Koranteng, Stephen (European Journal of Applied Sciences, 2025)
Perhaps, pathogens are the main biotic factor that cause diseases of plants reducing yield considerably. Man in its interest and effort tries to defend/protect these plants from the harassment by these pathogens. This review tries to look at the pathogen as a causal agent of diseases, disease development and the pathologist as management strategist employing various options to bring the pathogen under control. This initiative to unravel the causes of disease, disease development and management is seen as a “warfare” between the pathogen and the pathologist as each of them is seen to be smarter in its approach. Different strategies from both ends were examined and mechanisms by which each of them uses to outwit the other in this warfare are discussed. There is no doubt, the pathogen is far ahead and the most intelligent. It always tries to be a step ahead and seems to be dictating the pace with resultant nightmares/sleepless nights to the pathologist. The pathogen also tries to set the questions for the responses from the pathologist. Nevertheless, the pathologist has never relented in its effort to always find an antidote/solution to the swiftly and slippery nature of the pathogen. In nature’s own wisdom, perhaps it would be impossible for the pathologist to find a lasting antidote/solution, as this might appear to bring plant pathology as a profession to an end. The fight for supremacy therefore continues unabated.